PENGARUH MANAJEMEN STRATEGI PROGRAM KELAS INOVASI RELIGIUS TERHADAP KOMPETENSI KEAGAMAAN SISWA DI SMP NEGERI 1 SALAMAN - Ayu Anggraeni; Ida faridah; Mohamad Madum (STKIP Pesisir Selatan, 2026)
This study analyzes the influence of the strategic management of the Religious Innovation Class program on the religious competence of students at SMP N 1 Salaman using a quantitative approach. The type of research used is survey research because it is adjusted to the research objective of examining the effect of the independent variable, the influence of the strategic management of the Religious Innovation Class program, on the students' competence at SMP. The population consists of 60 students, using a saturated sampling technique where the entire population is taken as the sample. Data collection techniques in this study used questionnaires, documentation, and interviews, with instrument testing using validity and reliability tests. The data analysis technique uses prerequisite tests which include: classical assumption tests (normality, linearity, and heteroscedasticity), hypothesis testing using non-parametric analysis (Wilcoxon test). The results of the classical assumption test analysis show that the normality test is normally distributed if the value (p) > 0 ,05, namely (2) > 0.05), the linearity test results showed that it was not linear when (0.001 ≥ 0.05), the Wilcoxon hypothesis test results showed that (0.000 < 0.05), thus H₀ was rejected and H₁ was accepted.